Intercorrelations of Rock-Mass Classification Systems in Jakarta–Bandung High-Speed Railway Tunnel No. 6 - Yulianto, Muhammad Rahman (Jurnal Teknologi Pertambangan, 2025)
This study deals with the comparative investigation on various classification systems for sedimentary rocks, approximately 4,5 km long of the Highway Speed Railways Tunnel No. 6 Jakarta - Bandung. The results of extensive geotechnical explorations and field measurements were applied to obtain the rock mass classification systems such as Rock Mass Rating (RMR), Q-system (Q), and Rock Mass index (RMi) for a wide range of sedimentary rocks. A set of systems inter-relationship is proposed. So, it is proposed to find relations between any pairs of systems that both of them consider or not consider these parameters. The relations are proposed for a wide range of sedimentary rocks and can be applied for similar geological environments.